MNCs' HRM strategy and country of origin effect: Do North American, European and Japanese firms really differ? - Gyu-chang Yu; Woo-sung Park; Yung-ho Cho (Management Revue, 2007)
Based upon the sample of 419 MNCs' subsidiaries in Korea, we examined the country of origin effect in the choice of MNCs' HRM strategy: transplantation, localization, and mixed. A multinominal logit regression analysis showed that there is an important country of origin effect in the choice between a localization strategy and a mixed strategy. North American MNCS tended to implement mixed strategy, while Japanese MNCs tended to adopt localization strategy. European MNCs were in the middle. The estimated log odds of choosing a localization strategy over a mixed strategy by Japanese subsidiaries were 1.79 times higher than European subsidiaries and 2.85 times higher than N. American subsidiaries; those by European subsidiaries were 1.59 times higher than N. American subsidiaries. However, the country of origin was not significantly related to the choice between a transplantation strategy and other strategies. We also examined two alternative factors influencing the HRM strategy of foreign subsidiaries: investment strategy and entry strategy. The implications of this and directions for future research are discussed.
Keywords: 650; country of origin; HRM strategy; localization; MNCs; South Korea; Herkunftsbezeichnung; Personalmanagement; Regionales Cluster; Multinationales Unternehmen; Südkorea